Examination of physical and physiological parameters of national level boxers at age range of 11-13 - Güclüöver, A.; Tasbilek Yoncalik, M.; Sen, H. F.; Nur Sahin, I. (Journal of Education and Learning, 2019)
Delivering successful performance in sports depends on physical fitness. Unless the physical and physiological structure is in accordance with the requirements of the sports branch, a high performance in sports cannot be realized fully (Çakmakçi, 2002). Therefore, it is important to define and improve performance parameters such as body composition, anaerobic-aerobic endurance, capacity and strength in boxing. Accordingly, In this study, it is aimed to examine the physical and physiological fitness parameters of tiny natioanal boxers between 11-13 years of age. The research was carried out on 12 boxing athletes between 11-13 years of age in the tiny national category in Kirikkale province. In statistical analysis, normality was understood by Shapiro-Wilk test and descriptive statistics method was used to define the data. In this study, maximum oxygen consumption capacity (VO2) maxs, lung functional volumes, hand grip strength levels and body composition measurements of boxing athletes were evaluated. The mean of (VO2) max values of the participants were measured 44.17 ± 8.45. Also in correlation analysis, a high relationship was found at (VO2) max BMR; r = -750, p = 0.01 level between maximal oxygen consumption capacity and basal metabolic rate However, in oxygen consumption capacity and body composition variables, The negatively significant level relationships were found at levels of (VO2) max; body fat percentage (FM), r = -696, p = 0.05, lean body mass (FFM), r = -666, p = 0.05; body mass index (BMI), r = -763, p = 0.01). As a result, in this study, identification and relationship were determined about performance data in physical and physiological fitness parameters of tiny elite boxing athletes and a data about this age group was created in boxing athletes for future studies.